Experimental studies of an LHR mode DI diesel engine run on antioxidant doped biodiesel. (1st April 2022) - Pandey, Krishna Kumar; Paparao, Jami; Murugan, S.
Graphical abstract: Highlights: Antioxidant doped biodiesel is used as a test fuel in a coated engine. Combined effects of coating and antioxidants on engine behaviour are studied. The peak cylinder pressure increases by about 4.8% and similarly the peak heat release rate of the engine enhances by about 7.6%, after dosing DPPD. Fuel consumption and thermal efficiency improve by about 7.9% and 11.3% at full load serially, by adding of antioxidant. Abstract: In this research work, N, N'-Diphenyl-p-phenylenediamine (DPPD) as an antioxidant at various concentrations as 500, 1000, 1500, and 2000 ppm is dosed with Jatropha methyl ester (JME). The mixtures are tested in a naturally aspirated, constant speed, compression ignition (CI) engine. Yttria stabilized zirconia (YSZ), is coated on the piston crown of the test engine for converting it to a low heat rejection (LHR) engine. The engine characteristics in terms of combustion, emission, and performance of TBC piston-fitted engine run on antioxidant doped JME are evaluated at all engine loads. The experimental results are obtained for running the engine on the antioxidant doped JME conventional and LHR modes. By running the engine on antioxidant doped JME in the LHR mode, the heat release rate and the peak cylinder pressure rise by about 4.9% and 7.8%, respectively, at the maximum load condition. The carbon monoxide (CO) and unburned hydrocarbon (HC) emissions reduce to a maximum of 10.1% and 13.3%, serially, at maximum load operation; meanwhile, nitric oxide (NO) emission decreases by 13.6% at full load. The fuel consumption and thermal efficiency of the LHR engine improve by about 7.9% and 11.3%, respectively, at full load. The smoke opacity of the engine is decreased by about 8% at full load. All the obtained results are discussed in this research article.